Comparative Analysis of Physiological Responses in Two Ulva prolifera Strains Revealed the Effect of Eutrophication on High Temperature and Copper Stress Tolerance - Bao, Menglin; Park, Ji-Sook; Xing, Qikun; He, Peimin; Zhang, Jianheng; Yarish, Charles; Yoo, Hyun Il; Kim, Jang K. (Frontiers in Marine Science, 2022)
Climate change directly influences species composition and distribution of macroalgae on a global scale. Meanwhile, eutrophication and heavy metal pollution continue to be major concerns in coastal areas. The objective of this study was to explore interactive effects of these complex environmental conditions (high temperature, eutrophication and heavy metal pollution) in the bloom forming green alga, Ulva prolifera. This study evaluated the physiological characteristics of two strains of U. prolifera (Korean strain and Chinese strain) at two temperature levels (20℃ and 25℃), two nutrient concentrations (low nutrient: 50 μM of N and 5 μM of P; high nutrient: 250 μM of N and 25 μM of P) and three copper concentrations (Control (0.03 μM); 0.1 μM; 1 μM). Under the 20℃ and low nutrient condition, the Chinese strain grew significantly slower at 1μM copper group compared to copper control group. Whereas there was no significant change in the growth rate of the Korean strain. High nutrient significantly increased the growth rate, photosynthetic and respiration rates, soluble protein and tissue N in both strains at all copper groups under 20℃ compared to copper groups under 20℃and low nutrient condition. Both strains grew significantly slower at 1μM copper group compare to copper control group under high nutrient and 20℃ condition. 25℃ significantly reduced the growth rate of both strains at each nutrient condition. Under 25℃ and low nutrient condition, 1μM copper had no effects on growth rate and all photosynthetic parameters of both strains. Meanwhile, under 25℃ and high nutrient conditions, 1μM copper significantly inhibited growth and photosynthetic rates and increased soluble protein content in the Chinese strain compared to copper control treatment. These results suggest that the Korean strain had higher tolerance to the copper stress than the Chinese strain. Higher nutrient levels enhanced the temperature tolerance and the copper stress in U. prolifera. Increased temperature reduced the negative effects caused by copper stress in U. prolifera.